Pengembangan bahan ajar Pendidikan Agama Islam sub tema zakat, infak, sedekah dan hadiah fase C sekolah dasar - Alamsyah, Wahyu; Tanjung, Hendri; Ibdalsyah (TAWAZUN: Jurnal Pendidikan Islam, 2025)
Zakat, infaq, sedekah, and gifts are learning outcomes of Islamic Religious Education phase C of Elementary School with the implementation of 4 hours of study time every week. In the process of teaching and learning activities, the topic of zakat, infaq, sedekah, and gifts is difficult material for students as evidenced by the results of daily test scores. The minimal use of teaching materials is a challenge that must be faced and found a solution. This study aims to analyze the need for development of teaching materials, create teaching materials, determine the level of feasibility and effectiveness of teaching materials on zakat, infaq, sedekah, and gifts. The method used is the ADDIE RnD model. The results showed that 78% of students at SDN Harjamukti 1 and 64% of students at SDN Curug 2 agreed to the development of teaching materials on zakat, infaq, alms, and gifts. The feasibility of teaching materials on zakat, infaq, alms, and gifts in phase C of Elementary School was measured through a validation test. The validation results of material experts 3.8 are presented as 95%, the validation results of media experts 3.8 are presented as 95%, the validation results of language experts 3.7 are presented as 94%. The validation test results of material experts, media experts and language experts of teaching materials are classified as very feasible. The effectiveness of the use of teaching materials for zakat, infaq, alms and gifts at SDN Harjamukti 1 is classified as moderate with an N-Gain result of 0.68, while at SDN Curug 2 it is classified as high with an N-Gain result of 0.71. Abstrak Zakat, infak, sedekah dan hadiah adalah capaian pembelajaran Pendidikan Agama Islam fase C Sekolah Dasar dengan penerapan jam belajar 4 jam per pekan. Dalam proses kegiatan belajar mengajar, topik zakat, infak sedekah dan hadiah adalah materi yang sulit bagi peserta didik dibuktikan dengan hasil nilai tes ulangan harian. Minimnya pemanfaatan bahan ajar merupakan tantang yang harus dihadapi dan dicarikan solusinya. Penelitian ini bertujuan menganalisis kebutuhan pengembangan bahan ajar, membuat bahan ajar, mengetahui tingkat kelayakan dan efektivitas bahan ajar zakat, infak, sedekah dan hadiah. Metode yang digunakan ialah RnD model ADDIE. Hasil penelitian menunjukkan 78% siswa SDN Harjamukti 1 dan 64% siswa SDN Curug 2 setuju adanya pengembangan bahan ajar zakat, infak, sedekah dan hadiah. Kelayakan bahan ajar zakat, infak, sedekah dan hadiah fase C Sekolah Dasar diukur melalui uji validasi. Hasil validasi ahli materi 3.8 dipersentasekan menjadi 95%, hasil validasi ahli media 3.8 dipersentasekan menjadi 95%, hasil validasi ahli bahasa 3.7 dipersentasekan menjadi 94%. Hasil uji validasi ahli materi, ahli media dan ahli bahasa bahan ajar tergolong sangat layak. Efektivitas penggunaan bahan ajar zakat, infak, sedekah dan hadiah di SDN Harjamukti 1 tergolong sedang dengan hasil N-Gain 0.68, sedangkan di SDN Curug 2 tergolong tinggi dengan hasil N-Gain 0.71.